Cultural Heritage and Intergenerational Value Transmission: Waruga as a Sociocultural Learning Space in Minahasan Society - Siti Fathimah; Ferdinand Kerebungu; Bunyamin Maftuh; Qurratul Aini (Lembaga Bale Literasi, 2026)
This study aims to analyze the sociocultural values ??transmitted through Waruga and explain its role as a cultural learning space in Minahasa society. The study uses Spradley's ethnographic approach with research stages including participant observation, interviews, and documentation. Data collection was conducted at several Waruga sites in Minahasa, including Benteng Moraya Tondano, Waruga Mamarimbing, Waruga Kiwa, Waruga Timbukar, and the Minahasa Regent's Office area. The results show that Waruga not only functions as a traditional burial site, but also as a transmission of spiritual values, social values, and cultural identity values. These values ??are transmitted through family narratives, ancestral veneration rituals, ornamental symbols, cultural practices, and social interactions within the community. The research findings also indicate that Waruga has great potential to be developed as a source of sociological learning based on local wisdom to strengthen cultural literacy, identity awareness, and cultural preservation amidst the challenges of modernization and globalization. Thus, Waruga can be understood as a living cultural heritage that plays a role in maintaining the sustainability of the cultural values ??and identity of the Minahasa people.